PERENCANAAN PAJAK MELALUI PMK NO. 191/PMK.010/2015 TENTANG PERENCANAAN PAJAK UNTUK TUJUAN PERPAJAKAN (Studi Kasus pada PT. X, Rumah Sakit di Kepanjen- Kabupaten Malang) - Sari, Ernatalia (Jurnal Ilmiah Mahasiswa FEB, 2016)
The study aims to analyse the application of PMK No.191/PMK.010/2015 in tax planning through the revaluation of fixed assets for tax purpose. The method that used in this research isÂ  descriptive qualitative research with theoretical overview and as an object of research is PT. X. The data used in this research is quantitative data and qualitative data, data were obtained on primary and secondary data.The result showed that when PT. X perform revaluation of its fixed assets, will lead to difference between depreciation expense before and after the revaluation, in which the depreciation expense on fixed assets PT. X becomes larger. Depreciation expense increased after a revaluation would reduce the taxable income of the company, so the burden of tax to be paid by the company will be lower. Depreciations stars on 1 January 2016, so that its influence on the new corporate tax burden seen in 2016. Additionaly, it will give rise to a new tax burden on the excess of revaluation of fixed assets that will be taxed according the rates in PMK No. 191/PMK.010/2015, where the rates are much lower than the previous regulations.Key words: fixed assets revaluation, tax saving, tax planning.